Co-Deposition of Gold Nanoparticles and Metalloporphyrin Using the Langmuir–Blodgett (LB) Technique for Surface-Enhanced Raman Scattering (SERS). Issue 4 (April 2015) - Camacho, Sabrina A.; Aoki, Pedro H. B.; de Assis, Francisco F.; Pires, Ana M.; de Oliveira, Kleber T.; Aroca, Ricardo F.; Constantino, Carlos J. L.
The synergistic effect produced by metallic nanoparticles when incorporated into different systems empowers a research field that is growing rapidly. In addition, organometallic materials are at the center of intensive research with diverse applications such as light-emitting devices, transistors, solar cells, and sensors. The Langmuir-Blodgett (LB) technique has proven to be suitable to address challenges inherent to organic devices, since the film properties can be tuned at the molecular level. Here we report a strategy to incorporate gold nanoparticles (AuNPs) into the LB film by co-deposition in order to achieve surface-enhanced Raman scattering (SERS) of the zinc(II)-protoporphyrin (IX) dimethyl ester (ZnPPIX-DME). Prior to the LB co-deposition, the properties of the Langmuir monolayer of ZnPPIX-DME at the air-water interface, containing AuNPs in the subphase, are studied through the surface-pressure versus mean molecular area (π-A) isotherms. The ZnPPIX-DME+AuNPs π-A isotherm presented a significant shift to higher molecular area, suggesting an interaction between both ZnPPIX-DME molecules and AuNPs. Those interactions are a key factor allowing the co-deposition of both AuNPs and ZnPPIX-DME molecules onto a solid substrate, thus forming the LB film. SERS of ZnPPIX-DME was successfully attained, ensuring the spatial distribution of the AuNPs. Higher enhancement factors were found at AuNP aggregates, as a result of the intense local electromagnetic field found in the metal nanoparticle aggregates. The main vibrational bands observed in the SERS spectra suggest a physical adsorption of the ZnPPIX-DME onto the surface of AuNPs. The latter is not only in agreement with the interactions pointed out by the π-A isotherms but also suggests that this interaction is kept upon LB film co-deposition.